2012
DOI: 10.1037/a0025877
|View full text |Cite
|
Sign up to set email alerts
|

High Behavioral Approach System (BAS) sensitivity, reward responsiveness, and goal-striving predict first onset of bipolar spectrum disorders: A prospective behavioral high-risk design.

Abstract: A prospective, behavioral high-risk design provided a theoretically guided examination of vulnerability to first onset of bipolar spectrum disorder based on the Behavioral Approach System (BAS) model. Adolescents (ages 14–19) at an “age of risk” for bipolar disorder onset were screened on BAS sensitivity by interviewers blind to current symptoms, lifetime history, and family history of psychopathology. Participants were selected with high versus moderate levels of BAS sensitivity and administered a lifetime di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
226
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(235 citation statements)
references
References 115 publications
(207 reference statements)
8
226
0
1
Order By: Relevance
“…Both depressive and manic mood states have been associated with dysfunctions of the brain reward system (Alloy et al, 2012;Hasler, 2006;Johnson et al, 2012b). Previous studies have shown that bipolar patients exhibit increased behavioral and emotional responses to reward or its anticipation compared with healthy controls (Alloy et al, 2012;Gruber, 2011;Johnson et al, 2012aJohnson et al, , 2012b. However, bipolar patients do not appear to be faster to learn stimulus-reward associations (Johnson et al, 2012b;O'Sullivan et al, 2011) and even exhibit deficits in probabilistic reversal learning compared with healthy controls (Dickstein et al, 2010;Gorrindo et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Both depressive and manic mood states have been associated with dysfunctions of the brain reward system (Alloy et al, 2012;Hasler, 2006;Johnson et al, 2012b). Previous studies have shown that bipolar patients exhibit increased behavioral and emotional responses to reward or its anticipation compared with healthy controls (Alloy et al, 2012;Gruber, 2011;Johnson et al, 2012aJohnson et al, , 2012b. However, bipolar patients do not appear to be faster to learn stimulus-reward associations (Johnson et al, 2012b;O'Sullivan et al, 2011) and even exhibit deficits in probabilistic reversal learning compared with healthy controls (Dickstein et al, 2010;Gorrindo et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…Both depressive and manic mood states have been associated with dysfunctions of the brain reward system (Alloy et al, 2012;Hasler, 2006;Johnson et al, 2012b). Previous studies have shown that bipolar patients exhibit increased behavioral and emotional responses to reward or its anticipation compared with healthy controls (Alloy et al, 2012;Gruber, 2011;Johnson et al, 2012aJohnson et al, , 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…Favourable downward-comparisons are those where the outcome of the comparison shows that one's performance is better than that of someone else which usually enhance one's mood or selfesteem (e.g. Alloy et al 2012;Gibbons 1986;Joormann et al 2007;Meyer et al 2010). The opposite can occur when unfavourable upward-comparisons take place which means the comparison reveals that one has been outperformed by another person (Aspinwall and Taylor 1993;Major et al 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Risk propensity and impulsivity are associated with ADHD (Bakhshani 2013;Drechsler et al 2008;Shoham et al 2016), bipolar spectrum conditions (Alloy et al 2012;Reddy et al 2014;Strakowski et al 2010;Swann et al 2001), substance use disorders (Birkley and Smith 2011;Feldstein and Miller 2006;Kreek et al 2005;Lejuez et al 2010), and the cooccurrence of these conditions (Holmes et al 2009;Lee et al 2011;Moeller et al 2001;Upton et al 2011;Zuckerman and Kuhlman 2000). Akiskal et al (2005) studied 263 professionals affiliated with an outpatient psychiatric practice.…”
Section: Risk Propensitymentioning
confidence: 99%